Pengaruh Waktu Fermentasi terhadap Sifat Fungsional dan Warna Tepung Albumin Telur Itik - Dwiyati Pujimulyani; Sunar Andiwarsana; Suprapti Suprapti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
The objective of this experiment was to produce fermented duck egg albumin powder and to evaluate its functional properties and colour, as well. The fermentation of duck egg albumin at room temperature was done for 0, 6, 12, 18 and 24 hours, terminated with the addition of lactic acid 1 H 0.05% and drying in a cabinet drier at 45°C for 8 hours. The functional properties of duck egg albumin powder characterized were coagulant hardness, foaming capacity foam density. The results showed that fermented duck egg albumin powder had good functional properties and lighter colour. The 24 hours fermentation of duck egg albumin resulted in good powder with coagulant hardness of 0.04 mm, foaming capacity 355.84%, foam density 0.21 g/ml, colour intensity (OD 420 nm) 0.05, moisture content 7.95% (wb) and ash content 5.66% (db).